THE CONVERSATIONAL IMPLICATURE OF PODCAST ENTITLED “THE TRUTH ABOUT MONEY AND HAPPINESS” WITH DR SANA SAJAN - Ira Febriyanti Simanjuntak; Charles David Marudut Silalahi; Shancelldeep Kaur (Bajang Institute, 2025)
This study examines the conversational implicature in the podcast episode